2012
DOI: 10.1089/end.2011.0583
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing Combined Spongiosum Block and Intraurethral Lignocaine with Intraurethral Lignocaine Alone in Optical Internal Urethrotomy for Urethral Stricture

Abstract: Spongiosum block with intraurethral lignocaine has a better anesthetic effect than intraurethral lignocaine alone for performing optical internal urethrotomy. Spongiosum block with intraurethral lignocaine is a viable alternative for regional and general anesthesia in the management of anterior urethral stricture with optical internal urethrotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…[789] Data from the National Health Service in the UK during 2006 showed that the OIU or urethral dilatation was used in 93% of cases and urethroplasty in 7% of cases. [10] Optical internal urethrotomy has the advantage of ease, simplicity, speed, and short convalescence.…”
Section: Introductionmentioning
confidence: 99%
“…[789] Data from the National Health Service in the UK during 2006 showed that the OIU or urethral dilatation was used in 93% of cases and urethroplasty in 7% of cases. [10] Optical internal urethrotomy has the advantage of ease, simplicity, speed, and short convalescence.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of VIU remains widespread and popular among urologists because it is easy to perform, minimally invasive, and associated with shorter procedure time and less morbidity. 12 Many studies have shown good long-term outcomes of VIU for short-segment strictures with superficial spongiofibrosis. 13,14,15 When performed under local anesthesia, it reduces time in the operating theatre, cost and hazards associated with general or spinal anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…At 6 months follow-up, recurrent strictures were developed in three patients in Group 1 and five patients in Group 2. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] These can be overcome by combining topical lignocaine jelly into the urethra with ICSB as explained by Kumar et al . [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation